THE EVOLUTION OF MICROSCOPE (AEOS) EXOSCOPE IN THE WORLD OF ARTIFICIAL INTELLIGENCE AND ITS APPLICATION IN LUMBAR DISC HERNIATIONS SURGERY: A COMPREHENSIVE STUDY FROM HISTORICAL PERSPECTIVE TO CURRENT PRACTICES IN ROMANIA AT THE HOSPITAL ,,PROF.DR.N.OBLU”, IASI, ROMANIA - Lucian Eva; Maria-Raluca Munteanu; Mădălina Duceac (Covrig); Iulia Olaru; Constantin Marcu; Marius-Gabriel Dabija (Romanian Journal of Oral Rehabilitation)
Artificial Intelligence (AI) is a generic term that refers to the use of machines to model intelligent behavior with minimal human intervention. The “Prof. Dr. N. Oblu” Emergency Clinical Hospital, Iași, has a three-dimensional (3D) robotic digital microscope – exoscope (AEOS), which consists of a robotic arm useful during operations, emphasizing the benefits of artificial intelligence. The Aeos exoscope revolutionizes traditional microscopic procedures, providing high-quality stereoscopic images on a larger screen. The article presents the evolution of microscopes, the integration of artificial intelligence in medicine and the future potential of AI combined with advanced exoscopes in spine surgery and implicitly the development of quantification programs, necessary for further research for a more complex integration of AI. This study highlights the importance of preparing continuing medical education programs and integrated strategies in spine surgery centers.